Urban-Acquired Leptospirosis in Washington, DC: A Case Report and Review of the Literature. Issue 6 (November 2018) - Lerner, Andrea; Frost, Spencer; Siegel, Marc O.
Abstract : Abstract: Leptospirosis is rarely reported in the United States. Although primarily considered a disease of the tropics or of resource limited areas, leptospirosis is being reported more frequently in industrialized urban areas. We report a case of severe leptospirosis in a man living in Washington, DC, with occupational exposure to rats. A review of the literature was conducted, with a focus on the urban form of the disease, using the MEDLINE database from inception to May 2018.